Feminist Defiance in My Brilliant Career: Female Independence and the Rejection of MarriageFeminist Defiance in My Brilliant Career (1901): Female Independence and the Rejection of Marriage - Herin Ratnaningsih; Zhang Jiasheng (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2025)
This article examines Miles Franklin’s novel My Brilliant Career (1901) through a feminist and postcolonial lens, focusing on Sybylla Melvyn’s rejection of marriage and her efforts to achieve artistic autonomy amid the limitations of British settler colonialism. The novel subverts the Victorian ideals of womanhood- domestic, passive, and submissive—by featuring Sybilla, who defies patriarchal and colonial expectations. Drawing on the theories of Woolf and Spivak, this analysis highlights how Sybylla’s refusal to surrender her intellectual and economic independence to the institution of marriage reveals that feminist ambitions are inextricably intertwined with the formation of national identity in the Australian colonial context. Her struggle to define herself beyond the role of wife or daughter criticizes the doctrine of coverture and exposes gendered exclusions in the Australian literary canon. The study argues that My Brilliant Career articulates a proto-feminist spirit that not only defies colonial legacies but also demands a rereading of Australian national identity through the lens of women’s autonomy and resistance. Keywords: Australian colonial context, feminist, My Brilliant Career, rejection of marriage.